PERTUMBUHAN SEMAI MAHONI (Swietenia mahagoni (L) Jacq) PADA BERBAGAI TAKARAN PUPUK MAJEMUK NITROGEN POSPAT KALIUM - Asriani, .; Umar, Husain; Rahmawati, . (Jurnal Warta Rimba, 2018)
Mahogany has rapid growth and produces hard mahogany which is automatic for furniture. An important factor that determines the success of mahogany is the availability of quality seeds. For this reason, the things that need to be known are the availability of sufficient nutrients and air for seedling growth. In meeting the needs of seedlings, NPK compound fertilizers. The purpose of this study was to determine the growth of mahogany seedlings at various doses of NPK compound fertilizer. The research method is a Completely Randomized Design (CRD) consisting of four treatments, namely P0 = Land (control), P1 = Land + NPK fertilizer with a dose (5 g), P2 = Soil + NPK fertilizer at a dose (10 g) and P3 = Land + NPK fertilizer with a dose (15 g). Each treatment was repeated five times requiring 20 seedlings of 20 experimental samples, each polybag containing one mahogany seedling. The data used are the results of the analysis using in-depth or very realistic analysis and analysis using the Honest Real Difference Test (BNJ) at the level (5%). The results showed that the dose of NP fertilizer was very significant for all parameters, namely seedling height increase, stem diameter increase, number of leaves, seedling wet weight and seedling dry weight. Soil treatment + NPK fertilizer with a dose (15 g) (P3) gives the best influence on the growth of mahogany seedlings in almost all parameters that know, where the average seedling height increase, which is 2.40 mm, increase in stem diameter, ie 1.21 cm, increase in number of leaves, ie 3.03 strands, seedling wet weight, ie 2.75 g and seedling dry weight of 2.15 g.Keywords: NPK fertilizer, mahogany, Swietenia mahagoni (L) Jacq